Path Loss Models Optimization for Mobile Communication in Different Areas - Messaoud Gareh; Lotfi Djouane; Houcine Oudira; Nazih Hamdiken (Institute of Advanced Engineering and Science, 2016)
In mobile radio systems, path loss models are necessary for proper planning, interference estimations, frequencies assignments and cell parameters which are basic for network planning process. Empirical models are the most adjustable models that can be suited to different types of environments. In this paper, data collected in Batna, Algeria is used to calculate the path loss for GSM (908-957 MHz). The measured path loss is compared with theoretical path loss estimated by the most widely empirical models «Cost123», «Hata», «SUI» and «Egli». The best model to estimate the measured path loss is optimized using genetic algorithm to predict path loss for suburban and rural area. The RMSE and the other test criteria between the actual and predicted data are calculated for various path loss models. It turned out that the adjusted COST 231 model outperforms the other studied models. The investigated results can help telecommunication engineers improve their planning and design of microcellular system.